Metastatic melanoma: Surgical treatment of brain metastases – Analysis of 110 patients. (March 2020) - McHugh, Frances Anne; Kow, Chien Yew; Falkov, Anthony; Heppner, Peter; Law, Andrew; Bok, Ari; Schweder, Patrick
Highlights: Increasing rates of melanoma worldwide with New Zealand having one of the highest. In our population, BRAF mutation, solitary lesion and gross total resection confer survival benefit. WBRT did not show a significant improvement in overall survival in our population. Targeted and immuno-therapies show promising results. Abstract: New Zealand has one of the highest rates of melanoma in the world. In up to 10% of cases, the disease is metastatic at diagnosis. Cerebral metastatic involvement carries a particularly poor prognosis. 110 patients were included in the analysis. A retrospective consecutive series of patients treated surgically at Auckland City Hospital were studied, with parameters of demographics, tumour characteristics, surgery, pathology, systemic therapy and survival analysed. Mean age was 59.9 years (range 22–81 years). Median survival from date of surgery was 8.1 months (95% CI 6.9–9.4 months). Of the 58 patients tested for BRAF mutation, 28 were positive, similar to previously published data. This conferred a better prognosis with median overall survival of 12.3 months (95% CI 7.2–17.3 months) compared to 7.8 months (95% CI 5.6–10 months) for those who were negative (p < 0.05). Survival correlated positively with extent of surgical resection. Both BRAF positive status and targeted and/or immunotherapy were significant predictors of improved survival. In this cohort, radiation therapy did not show a statistically significant improvement in overall survival. Survival from resection of cerebral metastases from melanoma is improving. Survival benefit is conferred by BRAF mutation, solitary metastasis and gross total resection of lesion.